A new species of Pycnogonum Brünnich, 1764 (Arthropoda, Pycnogonida) from Flemish Cap (Northwest Atlantic Ocean) - Munilla, Tomás; Murillo, Francisco Javier; Soler-Membrives, Anna (Zootaxa, 2015)
A new pycnogonid species of the genus Pycnogonum is described from Flemish Cap (Northwest Atlantic Ocean) at 1453–1462 m depth. Pycnogonum bamberi sp. nov. is compared with its congeners, from which it can be distinguished by the combination of a glans-shaped proboscis, the low, transverse ridges that lie on the dorsodistal  surfaces of the first coxae and  femora of all legs and the distinctive conical tubercle on the mid-dorsal surface of the fourth segment of the trunk.